Comparison of the efficacy of chemotherapy and allogeneic hematopoietic stem cell transplantation for acute myeloid leukemia in first remission in adults - S. N. Bondarenko; I. S. Moiseev; I. A. Samorodova; T. L. Gindina; M. A. Kucher; O. A. Slesarchuk; L. S. Zubarovskaya; B. V. Afanasyev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
The aim of the study was to compare the efficacy of allogeneic hematopoietic stem cell transplantation (alloHSCT) and chemotherapy (CT) of acute myeloid leukemia (AML) in first remission (CR1), to identify factors influencing the results. We compare the efficacy alloHSCT in CR1 (n = 70) and CT (n = 52). Patients were stratified by age, the level of leucocytes, the origin of AML, cytogenetic risk group and response to induction CT. Five-years overall and disease-free survival (OS and DFS) were higher in the group alloHSCT (67 and 65 % vs 46 and 30 % (p = 0.02 and p = 0.001)). Benefits of DFS after alloHSCT was in standard and high-risk cytogenetic groups (78 % versus 29 % (p = 0.001), and 34 % vs 17 % (p = 0.007)). The risk of relapse (RR) was 24 % in patients after alloHSCT vs. 57 % for CT (p = 0.003). Comparing the RR after alloHSCT and CT depending on the cytogenetic risk groups: standard (HR0.2(CI95 %0.07 - 0.56) p = 0.002), and high (HR0.27(CI95 %0.08-0.86) p = 0.03). Additional factors affect the RR were the origin of AML (de novo) (HR0.47 (CI95 %0.3-0.74) p = 0.001), the hyperleukocytosis (HR1.91 (CI95 %1.09 - 3.32) p = 0.02), and no remission after the first course CT (HR3.32(CI95 %1.57-7.0) p = 0.002). The efficacy of alloHSCT compared with CT is higher both in standard and high-risk cytogenetic group.